CNS reservoirs for HIV: implications for eradication - Joanna Hellmuth; Victor Valcour; Serena Spudich (Elsevier, 2015)
Controversy exists as to whether the central nervous system (CNS) serves as a reservoir site for HIV, in part reflecting the varying perspectives on what constitutes a 'reservoir' versus a mere site of latent viral integration. However, if the CNS proves to be a site of HIV persistence capable of replicating and reseeding the periphery, leading to failure of virological control, this privileged anatomical site would need dedicated consideration during the development of HIV cure strategies. In this review we discuss the current literature focused on the question of the CNS as a reservoir for HIV, covering the clinical evidence for continued CNS involvement despite suppressive therapy, the theorised dynamics of HIV integration into the CNS, as well as studies indicating that HIV can replicate independently and compartmentalise in the CNS. The unique cellular and anatomical sites of HIV integration in the CNS are also reviewed, as are the potential implications for HIV cure strategies.